Modifikasi Permukaan Lapis Tipis Semikonduktor Ti02 Bersubstrat Grafit dengan Elektrodeposisi Cu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Surface modificationof graphitefT702has been done by mean of Cu electrodeposition. This research aims to study the effect of Cu electrodepositionon photocatalyticenhancing of Ti02.Electrodepositionhas been done using CUS04 0,4 M as the electrolyte at controlled current. The XRD pattern of modified Ti02 thin film on graphite substrate exhibited new peaks at 29= 43-440and 29= 50-510that have been identified as Cu with crystal cubic system, face-centered crystal lattice and crystallite size of 26-30 nm. CTABr still remains in the material as impurities. Meanwhile, based on morphological analysis, Cu particles are dissipated in the pore of thin film. Graphite/TiO~Cuhas higher photoconversionefficiency than graphite/Ti02. Keywords: semiconductor, graphite/Ti02> Cu electrodeposition